Metabolic Consequences of Infection of Grapevine (Vitis vinifera L.) cv. “Modra frankinja” with Flavescence Dorée Phytoplasma - Prezelj, Nina; Covington, Elizabeth; Roitsch, Thomas; Gruden, Kristina; Fragner, Lena; Weckwerth, Wolfram; Chersicola, Marko; Vodopivec, Maja; Dermastia, Marina (Frontiers in Plant Science, 2016)
Flavescence dorée, caused by the quarantine phytoplasma FDp, represents the most devastating of the grapevine yellows diseases in Europe. In an integrated study we have explored the FDp–grapevine interaction in infected grapevines of cv. ‘Modra frankinja’ under natural conditions in the vineyard. In FDp-infected leaf vein-enriched tissues, the seasonal transcriptional profiles of 14 genes selected from various metabolic pathways showed an FDp-specific plant response compared to other grapevine yellows and uncovered a new association of the SWEET17a vacuolar transporter of fructose with pathogens. Non-targeted metabolome analysis from leaf vein-enriched tissues identified 22 significantly changed compounds with increased levels during infection. Several metabolites corroborated the gene expression study. Detailed investigation of the dynamics of carbohydrate metabolism revealed significant accumulation of sucrose and starch in the mesophyll of FDp-infected leaves, as well as significant up-regulation of genes involved in their biosynthesis. In addition, infected leaves had high activities of ADP-glucose pyrophosphorylase and, more significantly, sucrose synthase. The data support the conclusion that FDp infection inhibits phloem transport, resulting in accumulation of carbohydrates and secondary metabolites that provoke a source-sink transition and defence response status.